The stabilization system of primary oscillation for a micromechanical gyroscope; Measurement Science and Technology; Vol. 28, № 6 : New Perspectives in Measurements, Tools and Techniques for systems - Baranov P. F. Pavel Fedorovich; Nesterenko T. G. Tamara Georgievna; Tsimbalist E. I. Edvard Ilyich; Vtorushin S. E. Sergey Evgenjevich (2017, 2017)
Title screen